Scattering by Cu adatoms between image-potential bands on Cu(001) - Boger, Klaus; Weinelt, Martin; Wang, Jinxiong; Fauster, Thomas (Applied Physics A-Materials Science & Processing, 2004)
With the increasing resolution and sensitivity of photoelectron spectroscopy, the influence of defects is becoming more and more obvious. Scattering processes induced by adsorbate atoms can be studied by time- and angle-resolved two-photon photoemission. We have examined the dynamics of electrons in image-potential states on the Cu(001) surface for statistically distributed Cu adatoms and have identified different scattering mechanisms. Scattering of electrons from the second (n=2) to the bottom of the first (n=1) image-potential band is observed, which we attribute to inelastic interband scattering with electrons in the bulk. At energies above the bottom of the n=2 band, resonant interband scattering from the n=2 to the n=1 image-potential band is found. The rate for these processes can be determined by modeling the time-resolved measurements via optical Bloch equations of a four-level system. Comparison of the transition and decay rates reveals that the decay rate of the n=2 electrons is almost exclusively changed by additional resonant interband-scattering processes upon adsorption.